Kelayakan Nasabah Dalam Menerima Pembiayaan di PT. BPRS Madina Mandiri Sejahtera Kota Yogyakarta - Faddly, Dina Laylla (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
Sharia Banking is everything related to Sharia Banks and Sharia Business Units, covering institutions, business activities, as well as ways and processes in carrying out its business activities (Article 1 of Law No. 21 of 2008 on Sharia Banking). The definition means that Sharia banking includes Sharia Commercial Banks (BUS), Sharia Business Units (UUS), and Sharia People's Financing Banks (BPRS). Sharia financing products are various in accordance with the needs of the community. Where sharia banks need to analyze each financing to reduce the risk of financing. The purpose of this research is to find out the feasibility of customers in providing financing to PT. BPRS Madina Mandiri Sejahtera Yogyakarta City. The type of research used is field. The nature of this research is descriptive cauldron. The research source uses primary data. Which can be directly by the manager of PT. BPRS Madina Mandiri Sejahtera Yogyakarta and secondary data used from company documents and other literature such as observation and documentation. In the results of the study using the 5C principle, namely; Character, Capacity, Capital, Collateral and Condition of Economy. With the concept of FAST, namely; Fathanah, Amanah, Shiddiq and Tabligh. As for the feasibility impact on the provision of financing, namely for the bank, this feasibility has a positive impact because with the feasibility, the bank can analyze in detail on the customer's request. As for the customer has a negative impact because to get capital quickly will be hampered by the existence of this 5C principle process. Keywords: Customer Eligibility, Financing dan PT. BPRS Madina Mandiri Sejahtera